IMPELEMENTATION OF THE UNFIELD MODELING LANGGUAGE MODEL IN THE CRIMINALITY DATA PROCESSING INFORMATION SYSTEM: IMPELEMENTATION OF THE UNFIELD MODELING LANGGUAGE MODEL IN THE CRIMINALITY DATA PROCESSING INFORMATION SYSTEM - Ali Akbar Ritonga; Ibnu Rasyid Munthe; Masrizal Masrizal (Institute of Computer Science (IOCS), 2020)
Implementation of Model Unfield Modeling Language in Information Systems Data Processing Criminality a system to provide information such as the report the complainant, witnesses, suspects, and criminal cases terjadi.sehingga help speed and quality in the provision of information. Unified Modeling results Langguage model implementation in the information system aims to facilitate the development of the information system which checks data processing, recording and reporting of data processed in digital form. This information system has access user is admin and user comprising leaders. This information system task criminality entering and storing data.